2023
DOI: 10.1186/s13059-023-02895-z
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering gene-family founder events during major evolutionary transitions in animals, plants and fungi using GenEra

Abstract: We present GenEra (https://github.com/josuebarrera/GenEra), a DIAMOND-fueled gene-family founder inference framework that addresses previously raised limitations and biases in genomic phylostratigraphy, such as homology detection failure. GenEra also reduces computational time from several months to a few days for any genome of interest. We analyze the emergence of taxonomically restricted gene families during major evolutionary transitions in plants, animals, and fungi. Our results indicate that the impact of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 102 publications
0
23
0
Order By: Relevance
“…We used an evolutionary transcriptomics approach to test the developmental hourglass hypothesis for the early development of the two Fucus species. We first collected stage-specific RNAseq data ( Table S1 ) and assigned phylogenetic ages to each protein-coding gene using GenEra (Barrera-Redondo et al 2023) ( Fig. S1 ).…”
Section: Resultsmentioning
confidence: 99%

A Transcriptomic Hourglass In Brown Algae

Lotharukpong,
Zheng,
Luthringer
et al. 2024
Preprint
Self Cite
“…We used an evolutionary transcriptomics approach to test the developmental hourglass hypothesis for the early development of the two Fucus species. We first collected stage-specific RNAseq data ( Table S1 ) and assigned phylogenetic ages to each protein-coding gene using GenEra (Barrera-Redondo et al 2023) ( Fig. S1 ).…”
Section: Resultsmentioning
confidence: 99%

A Transcriptomic Hourglass In Brown Algae

Lotharukpong,
Zheng,
Luthringer
et al. 2024
Preprint
Self Cite
“…Using a genomic phylostratigraphy approach (Barrera-Redondo et al 2023), we found that, overall, brittle star arm regeneration is mediated by ancient genes (i.e. metazoan or older; Figure 5A , Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, DENSE starts from the genome of the focal species and those of its neighboring species along with their corresponding phylogenetic tree. Then based on the phylostratigraphy calculated by GenEra (Barrera-Redondo et al, 2023), it predicts the date of emergence of all annotated coding sequences (CDSs) of the focal genome with the assumption that horizontal transfers are rare in eukaryotic species. To do so, GenEra screens each CDS against the nr database and the annotated CDSs of the neighboring genomes with DIAMONDv2 (Buchfink et al, 2021)(Figure 1A).…”
Section: Principle Of Densementioning
confidence: 99%
“…The latter correspond to genes found in a single species (i.e., orphan genes) or closely related species, a prerequisite for finding young de novo emerged genes. The detection of TRGs generally relies on phylostratigraphy that estimates the age of a gene of interest from the detection of its homologs across a phylogeny (Arendsee, Li, Singh, Seetharam, et al, 2019; Barrera-Redondo et al, 2023; Domazet-Loso et al, 2007). In practice, the idea is to screen each gene of the focal genome against a large sequence database (typically, nr or uniprot) with BLAST or an equivalent tool (Altschul et al, 1990; Buchfink et al, 2021).…”
Section: Introductionmentioning
confidence: 99%